Evaluating ERA5 reanalysis predictions of low wind speed events around the UK - Panit Potisomporn; Thomas A.A. Adcock; Christopher R. Vogel (Energy Reports, 2023)
Low wind speed events represent one of the biggest challenges in fully de-carbonising the electricity system due to the growing proportion of wind energy in the UK energy mix. While reanalysis products are a useful tool to study the spatio-temporal characteristics of these occurrences, their performance and limitations should be understood prior to usage. In this study, hourly 10 m ERA5 reanalysis wind speed data were evaluated against in-situ wind speed measurements from 205 onshore and offshore observation stations around the UK. It was found that ERA5 has biases in mean wind speed of 0.166 m/s and −0.136 m/s for onshore and offshore domains respectively, and biases in hourly wind speed standard deviation of −0.354 m/s and −0.425 m/s for onshore and offshore domains respectively. Both errors are more pronounced in autumn and winter. These errors lead to an underestimation of the percentage frequency of short-duration low wind speed events. Furthermore, the findings suggest that the largest errors are from sites which are situated in coastal and mountainous regions where short-range topographical variability and local wind effects may not be resolved by ERA5. Despite these shortcomings, ERA5 nevertheless outperforms its global reanalysis counterparts in the UK domain and therefore, can provide valuable information in the context of low wind speed events prediction.